SPECIFICITY OF IMMUNOTHERAPY FOR LINGERING AND RECURRENT RESPIRATORY DISEASES OF CHILDREN - N.D. Soroka (Union of pediatricians of Russia, 2008)
The article considers aspects of infectious diseases of respiratory tract of children in St Petersburg; determines the role of lingering and recurrent variations of the respiratory diseases; gives data on the basic factors of forming lingering and recurrent respiratory diseases. The article identifies the role of Immuno-correction in the treatment of unfavorably developing of bron chopulmonary diseases. It gives the findings of a clinical test of applying immuno-corrected medication with a high curative effect of the therapy.